Modelling Regional Scenarios for the Enlarged Europe European Competiveness and Global Strategies - Capello, Roberta; Camagni, Roberto; Chizzolini, Barbara; Fratesi, Ugo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
The aim of this book is to tackle the question of what the European territory will look like over the next fifteen years by providing quali-quantitative territorial scenarios for the enlarged Europe, under different assumptions on future globalisation strategies of BRIC (Brazil, Russia, India and China) and East and West European countries. The approach is as neutral as possible vis-à-vis the results, leaving to a new forecasting model, the MASST model, built by the authors, to produce the tendencies and behavioural paths of regional GDP and population growth in each individual European region under alternative assumptions on the competitiveness strategies of different blocks of countries. The results are accompanied by strong policy messages intended to encourage long-term strategic thinking among a wide range of actors, scientists and policy makers in response to the risks and opportunities that the European territory will face.
From Forecasts to Quantitative Foresights: Territorial Scenarios for an Enlarged Europe -- From Forecasts to Quantitative Foresights: Territorial Scenarios for an Enlarged Europe -- Theoretical and Empirical Underpinnings -- Space and Theoretical Approaches to Regional Growth -- Regional Competitiveness: Towards a Concept of Territorial Capital -- Space and Empirical Approaches to Regional Growth -- National and Regional Econometric Models -- Conceptual and Methodological Specifications -- The MASST Model: A Generative Forecasting Model of Regional Growth -- The Estimation Procedure: Data and Results -- The Simulation Procedure: The Algorithm, the Target Variables and the Stability of the Model -- Scenarios for the Enlarged Europe: Regional Quantitative Foresights -- Driving Forces of Change: The Baseline Scenario -- Global Challenges and European Strategies: Alternative Scenarios -- Territorial Images of the Future: The Quantitative Foresights Results -- Towards a Conclusion: Regional and Territorial Policy Recommendations.
Keywords: Leadership; Economic geography; Economics; Management science; Development economics; Economic growth; Regional economics; Spatial economics; Economics; Regional/Spatial Science; Business Strategy/Leadership.; Economics, general; Economic Growth; Economic Geography; Development Economics; Electronic books